11.0k views
5 votes
Describe what is being done in each step while solving the equation -2x + 6 +6x = 6 ( 2x -3 )

-2x + 6 + 6x = 12x - 18

4x + 6 = 12x - 18

6 = 8 × - 18

24 = 8x

3=x

please solve!​

1 Answer

10 votes

-2x + 6 + 6x = 6 (2x - 3) this is the equation

-2x + 6 + 6x = 12x - 18 distributive property has been applied

4x + 6 = 12x - 18 like terms have been added

6 = 8x -18 4x has been subtracted from both sides

24 = 8x -18 has been added to both sides

3 = x 8 has been divided from both sides

I hope this helps! Let me know if I need to explain more or if I got something wrong. Have a nice day!

User Sumit M Asok
by
6.1k points